2022
DOI: 10.1186/s42269-022-00925-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical ciliated cyst of the maxillofacial region: a systematic review

Abstract: Background The surgical ciliated cyst of the maxilla was initially reported as a sequela of Caldwell–Luc type open maxillary sinus procedures. Recently, other etiologies have become apparent and cases have been reported outside of the maxilla. They have the potential for local destruction and at times may mimic a locally aggressive tumor or cyst. We aim to elucidate the etiopathogenesis of the surgical ciliated cyst to improve prevention, diagnosis and treatment of these lesions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…POMC is more common in women than in men [11]. In this study, POMCs developed in 13 men and 16 women, with a higher predilection for women.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…POMC is more common in women than in men [11]. In this study, POMCs developed in 13 men and 16 women, with a higher predilection for women.…”
Section: Discussionmentioning
confidence: 51%
“…The lack of awareness of POMCs may lead to misdiagnosis as an odontogenic infection and delayed treatment. The average latency time was 4-22 years [11]. Owing to the long latency time, whether the clinical and radiologic features of POMCs may change over time need to be compared.…”
Section: Introductionmentioning
confidence: 99%
“…Other reported symptoms include nonspecific local swelling and discomfort frequently associated with a healthy mucosa [11,12]. Radiologically, the cyst appears as a round, radiolucent, unilocular lesion with defined borders, similar to other jaw cysts [9,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 97%
“…As suggested by many authors [11], prevention of PSCC can be possible with meticulous surgical technique, including suturing ripped nasal mucosa, removing sinus mucosa during orthognathic or facial trauma procedures, cleaning or changing the saw blades after maxillary osteotomy, avoiding entrapped mucosa between maxillary bones, doing mandible surgery first, and meticulous maintenance of the Schneiderian membrane in sinus lift.…”
mentioning
confidence: 99%
“…The traditionally accepted pathogenesis of surgical ciliated cysts involves entrapment of the nasal or maxillary sinus mucosa, a subsequent inciting inflammatory process, and progressively increased osmotic pressure.Together, these steps lead to cyst creation, expansion and enlargement. Classically associated with maxillary sinus surgeries (Gates et al, 2022), they have also been reported in association with orthognathic surgery (Hayhurst et al, 1993), bone graft (Nastri &…”
mentioning
confidence: 99%